Crime and social policy - Kemshall, Hazel, 1958- (Chichester, West Sussex, UK ; New York : John Wiley & Sons, 2013)
Crime and Social Policy provides an invaluable examination of the relationship between social policy and crime. It draws on recent empirical research to offer important insights into the impact of current social policy trends on the lives of offenders. Provides an invaluable examination of the critical relationship between social policy and crime managementIncludes illuminating case studies on the impact of social policies on offendersReviewscurrent social policy trends and their influence on crime causation, crime rates, and crime management>
6: Bleak Times for Children? The Anti-social Behaviour Agenda and the Criminalization of Social Policy7: Social Citizenship and Social Security Fraud in the UK and Australia; Index.
Includes index.
"Originally published as Volume 46, Issue 4 of Social Policy & Administration."
Print version record and CIP data provided by publisher.
Includes bibliographical references and index.
John Wiley and Sons
Keywords: Crime; Crime -- Sociological aspects; Crime -- Government policy; Social policy; x; Politique sociale; public policy; SOCIAL SCIENCE -- Criminology; Crime; Crime -- Government policy; Crime -- Sociological aspects; Social policy